2022
DOI: 10.1055/a-1806-4513
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the Nickel-Catalysed Hydrogenolysis and Cross-Coupling of Aryl Ethers

Abstract: The Ni-catalysed hydrogenolysis and cross-coupling of aryl ethers has emerged as a powerful synthetic tool to transform inert phenol-derived electrophiles into functionalised aromatic molecules. This has attracted significant interest due to its potential to convert the lignin fraction of biomass into chemical feedstocks, or to enable orthogonal reactivity and late-stage synthetic modification. Although the scope of nucleophiles employed, and hence the CC and Cheteroatom bonds that can be forged, has expande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 70 publications
(284 reference statements)
0
22
1
Order By: Relevance
“…Revised Catalytic Cycle(s). The set of energy profiles computed for the Ni-catalyzed cross-coupling under study suggests an interesting mechanistic scenario that differs from previously reported pathways 5,12,13 and that is summarized in Figures 7a and S15. It involves six key steps: (i) nickelate formation (1 → 4) through the complexation of two "ancillary" Ph groups to promote the release of one COD from Ni(COD) 2 and to enhance the electron donating ability of As mentioned above, the three nickelate complexes that feature all combinations of Ph and Naph groups are contributing to the overall selectivity and activity of the reaction and were thus included in kinetics simulations.…”
Section: ■ Computational Detailscontrasting
confidence: 54%
See 3 more Smart Citations
“…Revised Catalytic Cycle(s). The set of energy profiles computed for the Ni-catalyzed cross-coupling under study suggests an interesting mechanistic scenario that differs from previously reported pathways 5,12,13 and that is summarized in Figures 7a and S15. It involves six key steps: (i) nickelate formation (1 → 4) through the complexation of two "ancillary" Ph groups to promote the release of one COD from Ni(COD) 2 and to enhance the electron donating ability of As mentioned above, the three nickelate complexes that feature all combinations of Ph and Naph groups are contributing to the overall selectivity and activity of the reaction and were thus included in kinetics simulations.…”
Section: ■ Computational Detailscontrasting
confidence: 54%
“…With this mechanistic knowledge in hand, we next sought to use these insights to try and overcome a current challenge in Ni-catalysis, the so-called "naphthalene problem". 5 This phenomenon generally restricts the electrophilic coupling partner to πextended systems, such as 2-methoxynaphthalene, meaning that C−C cross-couplings of unbiased aryl ethers such as anisole itself are rare. 8−10 Computationally, the oxidative addition of anisole to Ni 0 -ate complex 4 accordingly to a mechanism analogous to the one computed for 2-methoxynaphthalene in the presence of [PhLi(THF)] 2 in benzene was assessed.…”
Section: ■ Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously explored the rich co-complexation chemistry of Ni(COD) 2 and PhLi, which gives a series of lithium nickelates including II (Scheme 1), and demonstrated that these are key intermediates in the nickel-catalysed cross-coupling of aryl ethers. 19,24 When further assessing these co-complexation reactions, we found that using a larger excess of PhLi led to the formation of a polynuclear dinickel cluster containing a bridging C 6 H 4 dianion as a result of intramolecular C-H activation of a phenyl substituent (Scheme 1, IV). 25 The formation of IV suggests that the homoleptic tri-lithium nickelate "Li 3 NiPh 3 (solv) 3 " is too electron-rich to form, leading to the in situ formation of the π-accepting benzyne-type ligand.…”
Section: Introductionmentioning
confidence: 99%